2012
DOI: 10.1186/1746-1596-7-95
|View full text |Cite
|
Sign up to set email alerts
|

N-cadherin is differentially expressed in histological subtypes of papillary renal cell carcinoma

Abstract: BackgroundPapillary renal cell carcinoma (RCC) represents a rare tumor, which is divided, based on histological criteria, into two subtypes. In contrast to type I papillary RCC type II papillary RCC shows a worse prognosis. So far, reliable immunohistochemical markers for the distinction of these subtypes are not available.MethodsIn the present study the expression of N(neural)-, E(epithelial)-, P(placental)-, und KSP(kidney specific)-cadherin was examined in 22 papillary RCC of histological type I and 18 papi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 40 publications
0
7
2
1
Order By: Relevance
“…In one study of papillary RCCs, membranous positivity for N‐cadherin was shown in all papillary RCCs of histological type II, while type I did not display any membranous expression for N‐cadherin. E‐cadherin, which is expressed in both types, exhibited a stronger immunopositivity in type II than in type I . The N‐ and E‐cadherin expression patterns in our case were different from these papillary RCCs.…”
Section: Discussioncontrasting
confidence: 60%
“…In one study of papillary RCCs, membranous positivity for N‐cadherin was shown in all papillary RCCs of histological type II, while type I did not display any membranous expression for N‐cadherin. E‐cadherin, which is expressed in both types, exhibited a stronger immunopositivity in type II than in type I . The N‐ and E‐cadherin expression patterns in our case were different from these papillary RCCs.…”
Section: Discussioncontrasting
confidence: 60%
“…Genetical analyses include gene copy numbers, chromosomal imbalances, gene mutations and single nucleotide polymorphism (SNP) analysis [18]. Many biomolecules, including epithelial-mesenchymal transition (EMT) markers such as N-cadherin [22] and vimentin [19] and human leucocyte molecules such as HLA-G and HLA-E [23], are reported to be biomarkers for renal cancer. Immunohistochemical examination of these biomarkers is important for the determination of the origin and the diagnosis of CDC.…”
Section: Discussionmentioning
confidence: 99%
“…However, the switch in expression from E-cadherin to N-cadherin and the higher expression of N-cadherin in patients with a poor prognosis were demonstrated in this study. Recent study also showed that N-cadherin was highly expressed in type II papillary renal cell carcinomas than type I cancers and type II cancers were related to poor prognosis [29]. …”
Section: Discussionmentioning
confidence: 99%